Advanced Electronics and Artificial Intelligence: Must‐Have Technologies Toward Human Body Digital Twins. (29th March 2022) - Dai, Yanning; Wang, Jiaqi; Gao, Shuo
Abstract : The development of precise virtual entities of human bodies has been pursued for many years, but to date, there have been few positive reports. In recent years, the success of digital twin (DT) technology in industrial applications has led to greater interest in establishing human‐body DT models. In particular, many recent advances in materials science, electrical engineering, and computer engineering have exhibited the intrinsic power of DT models in the detection and processing of complex body signals, indicating that the goals of establishing human‐body DTs are getting "within reach." Herein, current DT technologies in industry are discussed and advanced electronics and artificial intelligent algorithms are reviewed, which are must‐have building blocks for human DTs. Finally, perspectives on the use of human‐body DTs in improving the quality of life and introduction of never‐have immersive virtual reality experiences are discussed. Abstract : Recent advances in materials science, electrical, and computer engineering exhibit their intrinsic power in detecting and processing complex body signals, suggesting that the goal of establishing human body digital twins (DTs) is getting "within reach." Herein, must‐have building blocks for human body DT are reviewed and perspectives in improving life quality and bringing never‐have immersive virtual reality experience are drawn.